(untitled) (Journal of Hama University, 2021)
The aim of this study was: Isolate the Rhizobia from the chickpea plant, determine its biochemical characters and evaluate its antagonistic effect against Fusarium solani and Fusarium oxysporum in laboratory. The research was carried out in the laboratory of bacterial plant diseases in the Faculty of Agriculture-Damascus and in the glass house of the National Commission of Biotechnology for the agricultural season 2019 - 2020. Plant samples were collected from different locations of AS-Swaida governorate, Syria, 15 bacterial strains were isolated, the result of artificial infection showed that 10 isolates formed root nodes. The biochemical tests showed that they belong to Rhizobiaceae, Where They was Gram negative, Do not form spores, catalase positive, oxidase negative, able to use some sugars such as xylose, maltose, fructose, galactose, sucrose and mannitol as the source of carbon. they also metabolizes glucose and they are unable to metabolize lactose. some isolates decompose starch and others dissolve gelatin. Results of antagonist between Rhizobia isolates and tested fungi showed that the inhibition rate of tested fungi displayed differences in accordance with different fungi species and rhizobial isolate. However, the inhibitory effect of Rhizobia isolate (R1) and (R2) occurred most on medium growth of F. oxysporum 97.8% and 95.6% respectively, and moderate on F. solani (66.3%) and (65.5%). While, the inhibitory effect of The rest of rhizobial, isolated occurred High to Medium growth of All fungi tested. The data suggest that the Rhizobia isolates which are highly antagonist on Fusarium oxysporum Compared to Fusarium solani.